2023
DOI: 10.3389/fpubh.2023.1111889
|View full text |Cite
|
Sign up to set email alerts
|

Internet gaming disorder and aggression: A meta-analysis of teenagers and young adults

Abstract: Background and aimsInternet gaming disorder (IGD) and aggression (AG) are widespread phenomena around the world. Numerous studies have explored the relationship between the two but findings from such studies are inconsistent. The meta-analysis aimed to evaluate the relationship between IGD and AG as well as identify the variables moderating the relationship.MethodStudies investigating the relationship between IGD and AG were searched using selected terms to identify studies published from 1999 to 2022 on CNKI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…First, the prevalence of IGD in Asia is higher than in most Western countries ( Cho et al., 2017 ; Gao et al., 2022 ). This finding might reflect cultural features as studies have suggested, for example, that individuals may be weaker in self-monitoring in collectivist cultures than in individualistic cultures ( Li et al., 2023 ), although other possibilities exist. For example, roles for intrapersonal factors, including peer relationship, social support, or mental control from parents (parental psychological control may exert an indirect effect on adolescent IGD) also warrant consideration ( Zhuang et al., 2023 ).…”
Section: Discussionmentioning
confidence: 87%
“…First, the prevalence of IGD in Asia is higher than in most Western countries ( Cho et al., 2017 ; Gao et al., 2022 ). This finding might reflect cultural features as studies have suggested, for example, that individuals may be weaker in self-monitoring in collectivist cultures than in individualistic cultures ( Li et al., 2023 ), although other possibilities exist. For example, roles for intrapersonal factors, including peer relationship, social support, or mental control from parents (parental psychological control may exert an indirect effect on adolescent IGD) also warrant consideration ( Zhuang et al., 2023 ).…”
Section: Discussionmentioning
confidence: 87%
“…Probiotic administration in (preterm) infants has shown mixed results on neurocognition; two RCTs suggest long-term benefits in neurocognitive functioning in term infants, but larger RCTs are needed for robust evidence [ 48 , 49 ]. Recently, maternal VMT has shown promise to restore microbiota maturation and lead to better neurocognitive outcomes at 6 months of age in term infants born with cesarean-section [ 36 ▪▪ ], while safety and long-term results of maternal FMT to (preterm) infants are being explored in the MT-SECFLORE and PREFLORE trials [ 50 , 51 ].…”
Section: Modulating Gut Microbiota For Neurodevelopmentmentioning
confidence: 99%
“…Aggression in childhood and adolescence is a serious and pervasive problem, with its most severe forms occurring in this period. Research shows that increasing aggressive behavior is a particular concern with gaming addiction ( 1 ). With the development of technology, games have become a common amusement, particularly during the COVID-19 pandemic in which many adolescents were willing to dedicate most of their time to gaming.…”
mentioning
confidence: 99%